Women's work motivation and the influence on human capital development in Bhutan - Dayaram, Kandy; Liu, Yue (2016)
A plethora of studies focusing on the issues of society, women and work have largely centred around developed nations in western socio-economic contexts (Gregory and Milner 2009; Crompton 2006; Pocock 2003). Various other studies have focused around the experiences of women in the more developed regions of Asia where policy is largely driven around neo-liberal trends (Samad 2006; Tsui 2008; Mat Zin 2006). This paper explores the socio, political and cultural specificity of concepts such as, women, work, social norms and cultural traditions within Bhutan, which is unique in both its geography and national policy focus. Unlike its South East Asian counterparts where economic measures largely focus on gross domestic product (GDP) and wealth accumulation (Tsui 2008), Bhutan has come into the forefront of global attention with the conception of its national focus on improving the happiness index of the nation whilst simultaneously building its economic importance within the region. Bhutan has implemented specific interventions such as empowerment of women and formal policies aimed at removing workplace gender bias and improving gender equity (UNDP Bhutan Country Office 2007; Royal Government of Bhutan 2003). This study further explores the way that women approach the work terrain (Van Daalen, Willemsen and Sanders et al. 2006; Emslie and Hunt 2009) within the context of the experiences of women in a newly emerging formal workplace setting. It has been noted that country case studies “offer valuable lessons about the relationship between policy and organisational practice, as well as the cultural attitudes that underpin both” (Gregory and Milner 2009: 3). Indeed, studies that offer alternative perspectives on varying cultural approaches adopted to improve human development and labour participation rates enrich the existing body of literature (Marcinkus, Whelan-Berry and Gordon 2007, Greenhaus and Powell 2006). This study argues that social norms and cultural traditions in least developed countries (LDCs) and mainly agrarian economies, such as Bhutan (United Nations Conference on Trade and Development 2013) possess unique identities, for instance Bhutan influences women’s working experiences in different ways as compared to their counterparts in developed contexts. This paper attempts to highlight the issues surrounding the entry of Bhutanese women in the formal work sector. The study examines the following research questions: 1) How do Bhutanese women perceive their work motivation? 2) What are the roles of social norms and cultural traditions, and how have these impacted on women’s work lives? 3) What types of support do Bhutanese women receive to help them transition into the formal work sector?